OBTENTION OF PROTEIN CONCENTRATE AND POLYPHENOLS FROM MACADAMIA (MACADAMIA INTEGRIFOLIA) WITH AQUEOUS EXTRACTION METHOD - LARA D; VILCACUNDO E; CARRILLO C; CARPIO C; SILVA M; ALVAREZ M; CARRILLO W (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The aim of this study was to obtain protein concentrates from macadamia using alkaline pH at different pHs of precipitation with water to analyze the protein isolates using the Native-PAGE, SDS-PAGE electrophoresis and RP-UHPLC methods. Materials & Methods: Macadamia protein concentrates were obtained using the isoelectric precipitation method at different pHs using water as solvent. Proteins were analyzed using the Native-PAGE, SDS-PAGE electrophoresis and RP-UHPLC methods. Results: A yield of 36.57Â±0.17a of protein concentrate of defatted macadamia flour at pH 6.0 with a 51.564% of protein was obtained using the Dumas method. Polypeptides profile was identified in the 11-63 kDa range. Total polyphenols content was high at pH 5.0 with a value of 367,340 mg GAE equivalents / 100 g. Conclusions: Macadamia seed is a good source of proteins. Native-PAGE, SDS-PAGE and RP-UHPLC are good methods to identify the macadamia protein isolate in presence of water.Â Â